Study of institutional policies and didactic differences in the teaching of english among first grade students of public and private schools in the distric of David, Chiriquí, 2015 - Lezcano Morales, Lesbia Leticia (David, Panamá : UDELAS, 2015)
The study aims to analyze and compare the institutional policies of public and private schoold in the city of David. For the roles to by palyed by the administrative, teachers and students will be identified. It is also important to know: what are the academic goals for the year of the estudy? (2015)
TABLE OF CONTENTS TABLE INDEX GRAPHIC INDEX CHART INDEX FIGURE INDEX INTRODUCTION CHAPTER I. INTRODUCTORY FRAMEWORK 1.1. Background 1.2. Statement of the problem 1.3. Hypothesis 1.4. Objectives 1.4.1. General objectives+1.4.2. Specifics objectives 1.5. Justification 1.6. Scope and delimitation CHAPTER II: THEORETICAL FRAMEWORK Institutionals policies in public and private schools 2.1.1. Rules 2.1.1.1. Public school 2.1.1.2. Private school 2.1.2. Schedule 2.1.3. Subjects in english 2.1.4. Resources provied 2.2. Roles in the public and private education 2.2.1. Roles of the administrative 2.2.2. Roles of the teacher 2.2.3. Role of the students 2.3. Academic goals in public and private schools 2.3.1. Golas for first grade students 2.3.2. Competences 2.3.3. Linguistics skills 2.4. Didactic 2.4.1. Methodology 2.4.2. Strategies 2.4.3. Techniques 2.5. Learning english in basic level of education 2.5.1. Student's learning style 2.5.2. Multiple intelillences 2.6. Student's attitudes toward english langauge in learning context 2.6.1. Motivation 2.6.2. Discipline CHAPTER III: METHODOLOGICAL ASPECTS 3.1. Kind of research 3.2. Design of the research 3.3. Information sources 3.4. Population 3.4.1. Sample 3.5. Variables 3.5.1. Conceptual definition 3.5.2. Operational definition 3.5.3. Instrumental definition 3.6. Tools for data collection 3.6.1. Description of the instruments 3.6.2. Procedure CHAPTER IV: PRESENTATION AND ANALYSIS OF RESULTS 4.1. Outcome of the research 4.1.1. Interview with the principal 4.1.2. English teacher's survey 4.1.3. Student´s survey 4.1.4. Observation class CONCLUSIONS RECOMENDATIONS BIBLIOGRAPHY APPENDIXES
Incluye Table index
Incluye Graphic index
Incluye Chart index
Incluye Figure index
Documento presentado para optar por el Título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
Keywords: ENGLISH -- TESIS DE LICENCIATURA -- DIDACTIC; ENGLISH -- TESIS DE LICENCIATURA -- TEACHING; DOCENCIA EN INGLÉS; ESCUELA DE PEDAGOGÍA DOCENCIA DE INGLÉS